2020
DOI: 10.3389/fpsyt.2020.00269
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomic Profile and Signaling Pathway Prediction of Depression-Associated Suicidal Behavior

Abstract: Suicide is the most severe consequence of depression which has become a leading cause of disability and a global disease burden. Recent evidence indicates a central role of small molecules in the pathogenesis of depression and associated suicidal behaviors. However, there lacks a systemic exploration of small molecules in the development of depression-associated suicide, and it remains unclear how they affect an individual's behavior. In order to compare the metabonomic profiles between drug-naïve patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Numerous studies have shown that depression is an important risk factor for triggering SSIB and is strongly associated with suicidal ideation and behavior ( 20 22 ). Suicide is the most serious consequence of depression, where the prevalence of depression is about 2 to 9% ( 23 ). A Meta-analysis showed that the type of mental disorder most strongly associated with suicide attempts was depressive disorder ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that depression is an important risk factor for triggering SSIB and is strongly associated with suicidal ideation and behavior ( 20 22 ). Suicide is the most serious consequence of depression, where the prevalence of depression is about 2 to 9% ( 23 ). A Meta-analysis showed that the type of mental disorder most strongly associated with suicide attempts was depressive disorder ( 24 ).…”
Section: Introductionmentioning
confidence: 99%